PENGESAHAN BADAN HUKUM PERSEROAN TERBATAS DALAM PERATURAN PEMERINTAH TENTANG PERIZINAN BERUSAHA BERBASIS RISIKO (Online Single Submission Risk Based Approach) Ditinjau Dari Sifat Badan Hukum (Rechtpersoonlijkheid) - Hafizha Rika Nasution (Jurnal Hukum dan Bisnis (Selisik), 2022)
With the implementation of the ease of doing business (EoDB) in Indonesia, along with the enactment of Government Regulation No. 5 of 2021 regarding the Implementation of Risk-Based Business Licensing, which resulted in the implementation of the Online Single Submission Risk-Based Approach (OSS-RBA) program to obtain business permits for Limited Liability Companies. Through this program is one of the requirements in securing business legality in Indonesia. The purpose of this paper is to explain how the theory and concept of legal entities (rechtpersoonlickheid), especially Limited Liability Companies in Law no. 40 of 2007 regarding Limited Liability Companies and Law no. 11 of 2020 regarding Job Creation, then on the regulations in Indonesian law regarding the legal entity of Limited Liability Companies, especially about risk-based business licensing, and discusses the problems that arise as a result of the implementation of risk-based business licensing. The research method used is normative juridical. The results of the author’s research state that the regulation regarding the legalization of limited liability companies with government programs through risk-based business licensing is appropriate. The author can conclude that the theory and concept of the legal entity of a Limited Liability Company through the OSS-RBA program can make it easier for business actors to fulfill the legality of a Limited Liability Company. Furthermore, the author’s advice is to the Ministry of BKPM to review it, especially in the problems mentioned in this journal